Comparison of combined spinal-epidural anesthesia and femoral nerve combined with lateral femoral cutaneous nerve block anesthesia in elderly hip fracture surgery - Sun Jing; Shan Juanjuan; Qin Miaomiao; Liu Naihe (Guoji laonian yixue zazhi)
[Objective] To evaluate the comparative effects of combined spinal-epidural anesthesia and femoral nerve combined with lateral femoral cutaneous nerve block anesthesia in elderly hip fracture surgery. [Methods] A total of 140 elderly patients who underwent hip fracture surgery at the First People’s Hospital of Lianyungang City from March 2022 to March 2024 were selected and randomly divided into two groups using a random number table: the experimental group (femoral nerve combined with lateral femoral cutaneous nerve block anesthesia, n=70) and the control group (combined spinal-epidural anesthesia, n=70). Hemodynamics at different time points, duration of sensory and motor block, postoperative pain, cognitive function, serum levels, and complication rates were compared between the two groups. [Results] At T1, T2 and T3, MAP and HR in the test group were higher than those in the control group (P<0.05); at T1, T2 and T3, MAP in the control group was lower than that at T0 in this group (P<0.05), oxygen saturation in the two groups was higher than that at T0 in this group, HR was lower than that at T0 in this group (P<0.05); the onset time, perfection time and duration of sensory and motor block duration in the test group were longer than those in the control group (P<0.05); at 6 h, 12 h and 24 h after operation, the VAS score of the experimental group was lower than that of the control group, and the MMSE score was higher than that of the control group((P<0.05); at 6 h, 12 h and 24 h after operation, VASscore and MMSE score in the two groups were higher than those at 6h after operation in this group (P<0.05); the differences of IL-6, Aβ1-40 and S100β before and after operation in the test group were lower than those in the control group (P<0.05); the total incidence of complications in the test group was lower than that in the control group (P<0.05). [Conclusion] Femoral nerve combined with lateral femoral cutaneous nerve block anesthesia in elderly hip fracture surgery, compared with combined spinal-epidural anesthesia, can effectively prolong the block time, reduce postoperative pain, maintain more stable hemodynamic parameters, improve postoperative cognitive function, reduce the incidence of complications, with obvious clinical advantages.